Biomimetic Vasculatures by 3D‐Printed Porous Molds (Small 39/2022). Issue 39 (28th September 2022) - Ching, Terry; Vasudevan, Jyothsna; Chang, Shu‐Yung; Tan, Hsih Yin; Sargur Ranganath, Anupama; Lim, Chwee Teck; Fernandez, Javier G.; Ng, Jun Jie; Toh, Yi‐Chin; Hashimoto, Michinao
Abstract : Biomimetic Vasculatures In article number 2203426, Yi‐Chin Toh, Michinao Hashimoto, and co‐workers describe a microfluidics‐enabled molding technique to fabricate anatomically‐relevant vascular constructs using cell‐laden hydrogels. By using 3D‐printed porous molds of poly(ethylene glycol) diacrylate as casting templates, freestanding, branching, multilayered, and perfusable constructs are readily fabricated.